ANALISIS PENGARUH KECUKUPAN MODAL, KUALITAS AKTIVA PRODUKTIF DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA BANK KELOMPOK BANK UMUM BERDASARKAN KEGIATAN USAHA (BUKU) 4 - Ricky Talumantak (LPPM Universitas Asa Indonesia, 2019)
The purpose of this research is to provide empirical evidence about the relation of Capital Adequacy (CAR), Earning Assets Quality (NPL) and Liquidity (LDR) to bank profitability (ROA) in Indonesia especially for banks in Public Bank based on Business Acitivities called as Bank Umum berdasarkan Kegitan Usahan (BUKU) in 4 group. This research sample was extracted using purposive sampling method, comprising of the big 5 banks in Indonesia. The sample provided by 4th quarterly bank publication report for period of 2015-2018. Data analyzed by using multiple regression analysis and The result find that capital adequacy (CAR) and earning assets quality (NPL) have significant effect on bank profitability (ROA), but liquidity (LDR) have no significant effect on bank provitability (ROA). This research also find that CAR, NPL, LDR simultaneously have significant effect on bank profitability (ROA).